Maximum Element Corresponding Minimum Appears In Row Or Column Allotment Method To Appraise Enhanced Groom Pattern - et. al., S. Saravana Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, proposed methodology namely Maximum Element Corresponding Minimum Appears in Row or Column Allotment Method is justified to finalize the feasible solution with respect to minimize the cost from the basic feasible solution set for the transportation problems. The proposed methodology is a distinctive way to gain the feasible (or) may be optimal solution without interrupt the degeneracy condition.